PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Laia, Perwan (Universitas Nias Raya, 2024)
This research aims to examine the implementation of the Project Based Learning model in improving students' learning outcomes in Economics for Class X at SMA Negeri 1 Lahusa during the 2023/2024 academic year. The design used is a Classroom Action Research (CAR) design. The research instruments employed are student observation sheets and teacher observation sheets. Based on the research findings and discussions, it is shown that: (1) The results from cycles I and II indicate a significant improvement in student learning outcomes, which have reached an optimal level. (2) The Project Based Learning model can enhance students' learning outcomes in Economics, particularly in understanding economic issues related to human needs, scarcity, and economic systems. (3) In cycle I, the students' average score was 72.03, exceeding the minimum completeness criteria set by the education unit, which is 65. The percentage of student learning mastery in cycle I was 65.3%, which is categorized as not meeting the target optimally according to the learning objectives. Therefore, cycle II was conducted, resulting in an average score of 86.15 with a mastery percentage of 92.3%, categorized as very good. These results demonstrate significant improvement. The recommendation from this research is that teachers should consistently encourage and motivate students to be more active and think critically in understanding the concepts being studied, allowing teachers to act as facilitators who guide, summarize the taught material, and evaluate students' learning outcomes.